Biological performance of novel phosphate-based glass microspheres for mesenchymal stem cell therapy in osteoporotic patients - Gupta, Dhanak (2017)
In this study, degradable phosphate-based bulk or porous glass microspheres (BGMS or PGMS), with nominal molar compositions of P45-(45P2O5-16CaO-24MgO-11Na2O-4Fe2O3) and P40-(40P2O5-16CaO-24MgO-20Na2O), were evaluated for cytotoxicity, cytocompatibility and osteogenic potential for Mesenchymal stem cell (MSC)-based therapy in osteoporotic patients.